2009
DOI: 10.1002/clc.20644
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Decreases Myocardial Function as Evaluated Via Strain Imaging

Abstract: Objectives: The purpose of this study was to evaluate the effects of statin therapy on myocardial function as measured with echocardiography with tissue Doppler imaging (TDI) and strain imaging (SI) independent of its lipid-lowering effect. Background: Statin use is known to improve outcomes in the primary and secondary prevention of ischemic heart disease, but their use is also associated with myopathy, muscle weakness and in rare cases, rhabdomyolysis. We sought to evaluate whether TDI and SI is able to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The presence of metabolic syndrome [ 24 ], a primary focus of the two aforementioned studies in which statin therapy blunted adaptations, may have limited adaptations. In addition, reduced cardiac strain with statin use may be a contributing factor [ 25 ]. It is also worthwhile to consider the trends in the post-intervention data of the current study that reflect lower muscle oxidative capacity in the presence of chronic statin therapy despite the similar relative improvement ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of metabolic syndrome [ 24 ], a primary focus of the two aforementioned studies in which statin therapy blunted adaptations, may have limited adaptations. In addition, reduced cardiac strain with statin use may be a contributing factor [ 25 ]. It is also worthwhile to consider the trends in the post-intervention data of the current study that reflect lower muscle oxidative capacity in the presence of chronic statin therapy despite the similar relative improvement ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rubinstein et al . [ 23 ] showed that statin therapy in hypercholesterolemic patients for at least 6 months resulted in a small decrease in myocardial function of lateral wall (measured by TDI), which could be possibly due to statin-induced myopathy of cardiac muscle. However, another study demonstrated a significant improvement in LV systolic and diastolic velocities after 6 months of atorvastatin therapy with no such change in LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…However, these were in hypercholesterolaemic patients, so it is impossible to differentiate between improvement of serum cholesterol and direct effects on the myocardium. Interestingly, a recent study has shown that in normocholesterolaemic subjects, statin treatment improves myocardial function indexed by strain imaging [55] .…”
Section: Discussionmentioning
confidence: 99%